An analysis of fraud hexagon in detecting fraudulent financial reporting - Verolika, Nosa; Midiastuty, Pratana Puspa; Suranta, Eddy; Sari, Anggi Rulita (Proceeding International Conference on Accounting and Finance, 2024)
The aim of this study is to present empirical data regarding the impact of the fraud hexagon component on the identification of financial reporting fraud. Using the SPSS software, the investigation included logistic regression analysis. A sample of manufacturing companies that were listed between 2018 and 2022 on the Indonesia Stock Exchange was used in the study. The study's conclusions indicate that financial targets are less effective at identifying financial reporting fraud. The ability to detect dishonest financial reporting is positively impacted by financial target and ego. External pressure, opportunity, rationalization, capability, and collusion are the factors listed above; however, they have no bearing on identifying false financial reporting.